Limit Thinking and Boundary Rhetoric: A Genealogy of Borders - Karrer, Wolfgang (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The words “border,” “boundary,” and “limit” come up with surprising regularity in US critical discourse of the last thirty years or so, and it may be worthwhile to look at their history. Instead of dismissing them as merely partisan badges to carry around in conferences or as ironic allusions in popular culture and journalism, I will try to create a bilingual frame of reference for them. They have a common genealogy, and the discourses they occur in belong to certain formations. I will look at these three words, their distribution, multiple meanings, and the changes they undergo, mainly in the nineteenth and twentieth century. They may turn out to be cultural keywords that need further research along the lines that Raymond Williams has opened up for cultural studies (Williams; Jay; Koselleck 9-102). My main thesis is that the German words Grenze or Gränze (both spellings occur) in the texts of Friedrich Nietzsche (and his debts to Ralph Waldo Emerson, as I will argue below) form one of the main nodes for the contemporary use of “border—boundary—limit.” I will also look at related or opposite terms like “horizon,” “frontier,” “margin,” and others. A short conclusion, an “arbitrary closure,” will summarize the findings.